Improving the Junior Doctor Induction Programme in an NHS Trust - Udoka Onyechere; Harvir Sahota; Seetal Chavda; Toibat Adeyinka (BJPsych Open)
Aims: The aim of this Quality Improvement (QI) project was to enhance the induction programme for junior doctors at an NHS Trust, ensuring it is more meaningful and better prepares trainees for their psychiatry rotation.